The Communication Style of News Presenter in Building Audience Image and Trust on The Live Streaming Website Inewstv South Sumatra - Prismadarti, Anggun; Zinaida, Rahma Santhi; Wijayani, Isna (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2025)
Audience trust in news media is a crucial factor in building loyalty and credibility. The emergence of live streaming as a primary medium for news broadcasting has changed audience expectations, requiring news presenters to adopt effective communication styles that enhance trust and engagement. This study aims to analyze the communication styles employed by news presenters in establishing audience trust during live-streaming broadcasts on the Inewstv south sumatra website. Using a qualitative approach, this research employs in-depth interviews with news presenters and audience members, as well as direct observations of presenters' verbal and non-verbal communication styles during live broadcasts. Interpersonal communication theory and media image theory provide a framework for understanding how communication styles influence audience perception of credibility and trust. The findings reveal that an effective communication style characterized by clear language, expressive body language, appropriate tone modulation, and a balance between professionalism and relatability plays a significant role in shaping audience perception. Presenters who exhibit warmth, confidence, and interactivity are more trusted than those who appear rigid or overly formal. Integrating interactive elements in live streaming, such as real-time audience engagement, further enhances the perception of authenticity and transparency in news delivery. The implications of this study are expected to provide valuable insights for the broadcasting industry on improving communication quality and strengthening audience relationships through digital media. By understanding the role of communication style in fostering trust, news media can refine their strategies to deliver credible, engaging, and audience-centered content in an evolving digital landscape.